Aerosols characterization using satellite and ground based remote sensing during June 2013 haze episode over southern Peninsular Malaysia. Issue 1 (April 2020) - Latiff, Nur Atiqah Aainaa Abd; Machimura, Takashi
Abstract: Population and economic growth over the Southeast Asia region had triggered to the increasing of pollutant that been released by automotive emission, industrial activity or biomass burning. The occurrence of intense haze episodes become severe in every year degrading the surrounding air quality and reduce visibility which may cause economic loses. However, detailed study on the aerosols concentration, source and its properties remain a challenge due to the limitation of in-situ data. Therefore, this study aimed to analyse the aerosols properties over Southern Peninsular Malaysia by utilizing the satellite and ground based remote sensing. Thus, by emphasizing on 2013 intense haze episode, PM10 concentration combine with aerosols from Aerosol Robotic Network (AERONET) data and some environmental parameters, i.e. rainfall, visibility, and hotspot numbers were investigated. Southern Peninsular Malaysia experience a dry and dense condition in June 2013 with highest temperature with less rainfall were recorded. The aerosols concentration and properties through aerosol optical depth (AOD), Angstrom Exponent (AE) parameter and particle size distribut ion indicate the presence of fine aerosols during the June 2013 haze episode, which is associates with biomass burning aerosols. Meanwhile, the MODIS fire activity data represents more than 3000 hotspots were recorded over Sumatera region. HYSPLIT modelling shows the pollutant substance from biomass burning were transported to the study area on 21st of June 2013 from southwest area which mainly from the Sumatera area.